Evidence for polarons and itinerant carriers in superconductivity from time-resolved optical measurements on YBa2Cu3O7-Delta - Mihailovic, D; Stevens, C; Demsar, J; Podobnik, B; Smith, D; Ryan, J (1997)
Time-resolved optical relaxation measurements on time scales from 10(-13) to 10(-8) s as a function of energy (0.8-3 eV) and temperature give evidence for the existence of two different carrier relaxation processes, indicating the presence of two distinct electronic subsystems in the normal state in high-temperature superconductors, one exhibiting band-like relaxation properties and the other those of localized, polaronic states. Both components of the electrodynamic response exhibit significant changes at T-c, indicating that both carrier types may be involved in superconductivity. The experiments also show that both polarons and band-like carriers exist predominantly in the CuO planes, with an out-of-plane component of the order of 10-20% which is close to the experimentally observed occupancy ratio of holes of O ions of the CuO5 pyramids. Spectrally, the superconducting condensate is also found to be coupled to two distinct components in frequency (for both carriers): one below 0.1 eV and one in the range 1.5-2 eV, but with different anisotropies. A natural explanation of these datas is that the two types of carriers correspond to the two phases suggested by the structural data and as such present the first direct evidence of two-component superconductivity. The underdoped sample data can be interpreted as evidence of pre-formed pairs above T-c.